Personalised versus standard text message prompts for increasing trial participant response to telephone follow-up: an embedded randomised controlled retention trial - Herbert, Esther; Papaioannou, Diana; Loban, Amanda; Totton, Nikki; Hyslop, Marie; Bolt, Robert; Deery, Christopher (Current controlled trials in cardiovascular medicine, 2024)
Background Improving retention within randomised controlled trials is important. The effectiveness of different strategies can be assessed using a Study Within A Trial (SWAT). Previous research has shown personalised text message reminders improve clinic attendance rates; however, the results are mixed on improving postal questionnaire return. This SWAT aims to assess whether personalised text message reminders improve completion rates for scheduled telephone follow-ups. Methods This SWAT is a two-arm, multi-centre randomised controlled trial with equal allocation. The host trial was the Melatonin for Anxiety prior to General anaesthesia In Children trial (ISRCTN 18296119), where the child’s caregiver was to answer a scheduled telephone follow-up 14 days post-surgery; participants for the SWAT were therefore the caregiver. Text messages were sent 24–48 h before the scheduled call and the personalised version contained the first name of the caregiver which was omitted in the non-personalised version. The primary outcome was questionnaire completion rate, defined as the proportion of caregivers successfully contacted, and completed any of the questionnaires, over the telephone within the follow-up window (day 14 + 7 days). Results The SWAT included 100 of the 110 (91%) participants randomised into the host trial. Randomisation within the SWAT was equal between non-personalised ( n = 50) and personalised ( n = 50) interventions. The overall questionnaire response rate was 73% with a difference between the two interventions of 68% in the non-personalised text message arm and 78% in the personalised text message arm. The adjusted absolute risk difference was 7.1% (95% confidence interval = −10.2%, 24.4%). There was no difference in either the time to response or the number of contact attempts between the two interventions. Conclusions There is some evidence that personalised text messages could be effective at increasing response rates when data is collected via telephone and in a population of caregivers for paediatric trial participants. However, similar SWATs have shown mixed results. Given the low-cost and low risks associated with personalising text message reminders, this SWAT could be implemented easily in other RCTs scheduling telephone follow-up appointments. Trial Registration ISRCTN 18296119 , SWAT 35 (MRC Northern Ireland Network for Trials Methodology Network).